Eccentric, mature osseous cap: A distinct imaging feature of sinonasal osteoblastoma. Issue 2 (March 2018) - Dua, Sumeet G.; Locker, Philip H.; Rossi, Isolina R.; Jandali, Danny; Gattuso, Paulo; Batra, Pete S.; Tajudeen, Bobby A.
Background: With the exception of osteomas, bone neoplasms that originate in the sinonasal cavity are seldom diagnosed on preoperative imaging due to a lack of characteristic radiographic features. Here we described the unusual occurrence of an osteoblastoma in the paranasal sinuses, and we drew focus to its salient imaging features. A highly unique imaging sign was indicated, and its pathologic basis was explained, with concurrent review of the literature. Methods: Case series and review of the literature. Results: Two cases of sinonasal osteoblastoma were managed by definitive surgical resection. Both tumors on preoperative computed tomography demonstrated an expansile, heterogeneous fibro-osseous lesion with an eccentric, mature osseous cap. The dense osseous cap seen on imaging corresponded to a rim of mature bone on histopathology. A review of existing literature revealed the presence of this imaging sign in all reported cases. Conclusion: Sinonasal osteoblastoma is an extremely rare entity with undefined imaging characteristics to guide preoperative decision-making. Here we reported, to our knowledge, the first description of a characteristic imaging sign of an eccentric, mature osseous cap, which corresponded histologically to a single peripheral layer rim of osteoblasts, a unique trait of osteoblastoma.